TIMOMEGALIA IN CHILDREN COMBINED WITH BRONCHIAL OBSTRUCTION SYNDROME: REVIEW ARTICLE - Burkhanova Dilovar Sadriddinovna (Web of Journals Publishing, 2025)
Timomegalia is the enlargement of the thymus gland, most commonly detected in young children, especially in the neonatal and early childhood periods. Despite the fact that the thymus plays a key role in the formation of the immune system, its pathological enlargement can lead to respiratory disorders, especially in combination with bronchial obstruction syndrome (BOS). This review article examines the clinical aspects, pathogenetic mechanisms, diagnostic methods, and treatment approaches for thymomegaly in children with bronchial obstruction syndrome.
Keywords: Bronchoblastic syndrome, diagnostics, thymomegaly, immune system, lymphocytes.